1990
DOI: 10.1093/nar/18.19.5775
|View full text |Cite
|
Sign up to set email alerts
|

The specific binding of nuclear protein(s) to the cAMP responsive element (CRE) sequence (TGACGTCA) is reduced by the misincorporation of U and increased by the deamination of C

Abstract: Point mutations in the cAMP-responsive element (CRE) of the rat somatostatin gene promoter/enhancer sequence (TGACGTCA) were used as a model for assessing the effect of uracil, deriving either from misincorporation during DNA synthesis (T----U) or cytosine deamination (C----U), on the binding of sequence/specific regulatory proteins. The results show that the T----U conversion in both strands of the CRE palindromic sequence reduces its affinity for the CRE binding factor(s), suggesting the crucial role of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 21 publications
(21 reference statements)
2
48
0
Order By: Relevance
“…The absence of the 5-methyl group in uracil has the potential to alter DNA structure and dynamic features that might be important for recognition by transcription factors or other DNA binding proteins (23,25). For example, uracils localized in the origin of replication in HSV-1 were found to perturb the binding of the HSV-1 origin binding protein (27), and incorporated uracils in the cAMP response element (CRE) of rat stomatostatin gene led to a two-to fourfold decrease in binding of CRE binding proteins from HeLa extracts (26). Our observation of reduced GFP expression from the exogenously uracilated DNA in the HT29-Ugi cell line supports the proposal that the presence of uracil in DNA can lead to reduced gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the 5-methyl group in uracil has the potential to alter DNA structure and dynamic features that might be important for recognition by transcription factors or other DNA binding proteins (23,25). For example, uracils localized in the origin of replication in HSV-1 were found to perturb the binding of the HSV-1 origin binding protein (27), and incorporated uracils in the cAMP response element (CRE) of rat stomatostatin gene led to a two-to fourfold decrease in binding of CRE binding proteins from HeLa extracts (26). Our observation of reduced GFP expression from the exogenously uracilated DNA in the HT29-Ugi cell line supports the proposal that the presence of uracil in DNA can lead to reduced gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of uracil in DNA can affect DNA dynamic conformation as well as sequence-specific protein binding (28). Nonetheless, it has been reported that the major measurable consequences of high levels of uracil in DNA are lesions created by the attempt of cells to remove this nucleotide (29).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deletion of HCMV UNG delays and diminishes replication of the virus in serum-deprived primary human fibroblasts (10). HSV-1 UNG (UL2 product) was first reported to be dispensable for viral replication in tissue culture (46), but later evidence suggested that the protein is required for virus reactivation from latency and for efficient replication in nerve tissue, which contains very low levels of cellular UNG (19,55,74).…”
mentioning
confidence: 99%